REPRESENTASI PERDAMAIAN DUNIA DALAM LIRIK LAGU IMAGINE OLEH JOHN LENNON - Adhi Prasetyo, Sasmandanu; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2020)
Representation is a picture or sign of a meaning in a message. Music is a medium that can deliver messages to audiences on a large scale, Like the message about world peace contained in John Lennon's song Imagine, this research aims to analyze how the representation of world peace is contained in John Lennon's song Imagine. This research method uses qualitative research, qualitative research aims to explain phenomena in depth by collecting data and this research also uses a constructivist paradigm. The theory in this study uses Ferdinand De Saussure's theory where this theory has the principle that language is a sign system, and each sign is composed of two parts, namely the signifier and the signified. The results of this study indicate that in the song Imagine describes the causes of conflict that keep the world away from peace.   Keyword : Representation, World Peace, Music, John Lennon, Imagine, Ferdinand De Saussure.